Evaluating monetary policy measures in a small primary-exporting economy - Watson, Patrick Kent ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1999)
Seeks to determine empirically whether and to what extent monetary policy impacts the real sector in Trinidad & Tobago given the great dependence on oil.